Inhibition of NMDA receptor function with an anti-GluN1-S2 antibody impairs human platelet function and thrombosis. (17th November 2017) - Green, Taryn N.; Hamilton, Justin R.; Morel-Kopp, Marie-Christine; Zheng, Zhaohua; Chen, Ting-Yu T.; Hearn, James I.; Sun, Peng P.; Flanagan, Jack U.; Young, Deborah; Barber, P. Alan; During, Matthew J.; Ward, Christopher M.; et al.
Abstract: GluN1 is a mandatory component of N -methyl-D-aspartate receptors (NMDARs) best known for their roles in the brain, but with increasing evidence for relevance in peripheral tissues, including platelets. Certain anti-GluN1 antibodies reduce brain infarcts in rodent models of ischaemic stroke. There is also evidence that human anti-GluN1 autoantibodies reduce neuronal damage in stroke patients, but the underlying mechanism is unclear. This study investigated whether anti-GluN1-mediated neuroprotection involves inhibition of platelet function. Four commercial anti-GluN1 antibodies were screened for their abilities to inhibit human platelet aggregation. Haematological parameters were examined in rats vaccinated with GluN1. Platelet effects of a mouse monoclonal antibody targeting the glycine-binding region of GluN1 (GluN1-S2) were tested in assays of platelet activation, aggregation and thrombus formation. The epitope of anti-GluN1-S2 was mapped and the mechanism of antibody action modelled using crystal structures of GluN1. Our work found that rats vaccinated with GluN1 had a mildly prolonged bleeding time and carried antibodies targeting mostly GluN1-S2. The monoclonal anti-GluN1-S2 antibody (from BD Biosciences) inhibited activation and aggregation of human platelets in the presence of adrenaline, adenosine diphosphate, collagen, thrombin and a protease-activated receptor 1-activating peptide. When human blood was flowed over collagen-coated surfaces, anti-GluN1-S2 impaired thrombus growth and stability. The epitope of anti-GluN1-S2 was mapped to α-helix H located within the glycine-binding clamshell of GluN1, where the antibody binding was computationally predicted to impair opening of the NMDAR channel. Our results indicate that anti-GluN1-S2 inhibits function of human platelets, including dense granule release and thrombus growth. Findings add to the evidence that platelet NMDARs regulate thrombus formation and suggest a novel mechanism by which anti-GluN1 autoantibodies limit stroke-induced neuronal damage.